Ignition Delay Period Prediction for Compression Ignition Engines Fueled with Ethanol/Diesel Blends (Journal of Engineering, 2024)
A key characteristic of diesel engines is predicting the ignition delay period. This work predicts the ignition delay in diesel engines using combinations of ethanol/diesel fuel blend and pure diesel as fuel replacements. It provides an empirical formula for predicting delay periods.  A growing interest in alternative fuel blends, representing a substantial shift from the use of traditional diesel fuel, is reported. Modern study is focused on examining these combinations and how they might affect the dynamics of combustion in diesel engines. Experiments were carried out utilizing five different ethanol/diesel fuel blends, including pure diesel, with ethanol percentages varying from 5% to 20% in 5% quantities. Tests were conducted at a constant engine speed of 1,500 rpm, with various compression ratios of 16, 17, and 18, with torque levels ranging from 0 to 21 N.m. In this study, general formulas for predicting ignition delay are constructed numerically. There was a greater consistency between the experimental outcomes and the expected ignition delay. The findings indicated that the E20 combined fuel continuously exhibited the least igniting delay period across all compression ratio variables. The findings demonstrated that the ignition delay period starts to shorten with increased cetane number, ignition pressure, temperature, and equivalency ratio. A shorter period of ignition delay is the outcome of higher compression ratios. The predictive model created here is a ground-breaking addition to the industry, offering a solid foundation for assessing the efficiency and emissions properties of different ethanol/diesel blends.